PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS X SMAN 1 BANUHAMPU - Annisa Mahendra (Jurnal Edukasi dan Penelitian Matematika, 2021)
Understanding mathematica1 concepts is 0ne 0f the learning objectives that must be mastered by students. However, in reality at SMAN 1 Banuhampu, the ability t0 understand the c0ncepts of class X students still needs to be improved. One 0f the fact0rs that causes this to happen is 1earning that has n0t been fully able t0 facilitate students t0 devel0p a good understanding of concepts. One 0f the efforts t0 impr0ve students' understanding 0f mathematical concepts is t0 apply the C0ntextual Teaching and Learning (CTL) appr0ach. The purp0se of this study was t0 identify and describe the impact 0f applying the Contextual Teaching and Learning approach to the ability to understand mathematical concepts of the tenth graders of SMAN 1 Banuhampu. The type of research used is pre-experimental with One Sh0t Case Study Design. The subject 0f this research is class X MIPA 4 SMAN 1 Banuhampu. The instrument used is a test of the ability to understand mathematical concepts in the form of description questions, the data obtained are then analyzed based 0n the percentage 0f the number 0f students and the average value of students per indicator. Based 0n data analysis, it can be c0ncluded that the development of the ability t0 understand mathematical c0ncepts 0f students in class X MIPA 4 SMAN 1 Banuhampu with the application of the CTL approach is very good and has increased in several indicators, namely indicators restating concepts, identifying properties of operations or concepts, applying concepts logically, giving examples and non-examples of c0ncepts, and presenting concepts in various f0rms of mathematical representati0n. Keywords –Ability t0 Understand Mathematical C0 ncepts, CTL Approach, One Shot Case Study Design.